Cage occupancy of methane clathrate hydrates in the ternary H2O–NH3–CH4 system. Issue 82 (16th September 2020) - Petuya, Claire; Choukroun, Mathieu; Vu, Tuan H.; Desmedt, Arnaud; Davies, Ashley G.; Sotin, Christophe
Abstract : Suggested effect of NH3 on methane cage occupancy. Abstract : The incorporation of ammonia inside methane clathrate hydrate is of great interest to the hydrate chemistry community. We investigated the phase behavior of methane clathrate formed from aqueous ammonia solution. Ammonia's presence decreases methane occupancy in the large cages, without definitive Raman spectroscopic evidence for its incorporation inside the structure.